ANALISIS KONSEKUENSI KUALITAS LAYANAN FISKUS TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK PPH DALAM MEMENUHI KEWAJIBAN PAJAKNYA - Pratiwi, Hanna (Jurnal Ekobistek, 2012)
Analysis Consequences Quality Service Tax Authorities Against the Level Obedience Assessable Income Tax in Meet Obligation Tax. Mentors I Elfiswandi, SE, MM, Ak and mentors II Hanna Pratiwi, SE, MM. The study examined officer servis tax perceptions of againts the level obedience assessable. The purpose of this study to find out how officer servis tax perceptions of against the level obedience assessable income tax in meet obligation tax. Respondents in the study were samples of the pharmacies population in Padang City obtained by incidental sampling, a total of 40 pharmacy who is still active until the year 2012. The data was collected in November 2011. All data have been collected in the first test of validity (Pearson moment) and reliability (Cronbach alpha). In the first hypothesis test used t-test to know is the model regression variables partially influential against obedience assessable, in view of the value thitung < ttable, while for the second hypothesis test used F-test with know is an independendent variable together influential significantly against variable dependent, with a significance level of 0.05. The results of this study indicate that servis tax already have perceptions positive obedience assessable (pharmacy) in variable reliability, responsiveness, empathy, tangibles and there not influence in variable assuarance. Finally, the authors suggest to the service tax to increase ability a more in raise confidence assessable (pharmacy).